Expression of STK15, CENPW and TIMP1 genes in breast and colorectal cancers from human blood samples - Goh, Lucky Poh Wah (2015)
Cancer is one of the highest incidence and mortality worldwide. Despite the great information on cancer, particularly in breast cancer (BC) and colorectal cancer (CRC), the rate of BC and CRC incidence and deaths remains alarming. This pilot case-control study is conducted to further understand the biology of cancer especially in mRNA/gene expression aspect using whole blood system by analyzing the differential gene expression of three potential BC and CRC related genes which were STK15, CENPW, and TIMP1. Whole blood samples were collected from 31 healthy individuals and 36 cancer patients (14 BC and 22 CRC) followed by total RNA isolation using Tempus™ Blood RNA System. The RNA integrity number (RIN) of extracted RNA was determined using bioanalyzer. Gene expression analysis was performed with 5’-hydrolysis probes in triplicates using real-time PCR. Additionally, influence of other factors such as age, gender, and gene polymorphism to gene expression were also evaluated in this study. Statistical Mann-Whitney U-test was applied to determine the differential expressions of STK15, CENPW and TIMP1 normalized to two reference genes (GAPDH and HPRT1) in BC and CRC patients, with p<0.05 as statistical significant. This study showed that the extracted total RNA was highly intact with RIN>7.0 for reliable gene expression analysis. STK15 expression was significantly (p<0.05) downregulated in CRC regardless of both age and gender. Interestingly, a significant (p<0.05) reduction of STK15 expression of BC were found in age ≥50 but not in age <50 suggesting an age related factor in BC and not in CRC. No significant difference was observed in the downregulation of CENPW and TIMP1 gene expression in BC and CRC. Further investigation based on genotyping of the STK15 Phe31Ile polymorphism showed that STK15 expression in BC was non-significantly (p>0.05) downregulated after samples were grouped according to genotypes (Phe/Phe, Phe/Ile, and Ile/Ile), but significant (p<0.05) downregulation was observed in CRC patients carrying homozygous wild-type (Phe/Phe) or homozygous variant (Ile/Ile) genotypes. This indicated Phe/Phe or Ile/Ile genotype in STK15 Phe31Ile polymorphism associated to reduce STK15 expression in CRC but not in BC. In summary, the reduced STK15 expressions of this study provide an initial insight of using blood-based biomarker for BC and CRC.